O maior desastre climático do Brasil: chuvas e inundações no estado do Rio Grande do Sul em abril-maio 2024 - Marengo, José A. [UNESP]; Dolif, Giovanni [UNESP]; Cuartas, Adriana; Camarinha, Pedro; Gonçcalves, Demerval; Luiz, Rafael; Silva, Larissa; Alvala, Regina C.S. [UNESP]; Seluchii, Marcelo E.; Moraes, Osvaldo L. [UNESP]; Soares, Wagner R.; Nobre, Carlos A. (FapUNIFESP (SciELO), 2024)
The unprecedented 2024 April-May floods in the State of Rio Grande do Sul have affected over 90% of the state, displacing hundreds of thousand people and causing 171 deaths. The El Niño Southern Oscillation phenomenon was found to be important to explain the variability in the observed rainfall, consistent with previous research that show previous heavy rainfall events in the area occurred during El Niño years. Cold front fronts bringing rainfall remained stationary over southern Brazil, since they could not move into central Brazil because of atmospheric blocking with warm and dry air and highest temperatures in that region. The flood event in Porto Alegre was triggered by heavy rainfall over the Lake Guaíba Basin, with accumulated surpassing 500 mm in 5 days, leading to record high levels of 5, 35 m on May 5, highest that the previous flood in 1941. In addition to the extreme nature of this event, this contributed to the significant impacts of flooding in vulnerable areas of the Porto Alegre Metropolitan Region and nearby municipalities. This highlights the need to objectively assess risk and reinforce flood infrastructure to increase resilience to this and future, even more extreme, floods.
Keywords: Climate change; Climate variability; Desastre; Disaster; Enchentes; Floods; Impact; Impacto; Mudanças climáticas; Risco; Risk; Variabilidade climática